Alternative Methods of Fixation for Anterior Tibialis Transfer in Residual Clubfoot Deformity - Spencer Wilson, BS; Laura L. Bellaire, MD; Kenneth J. Noonan, MD, MHCDS (Elsevier, 2024)
The preferred treatment for congenital clubfoot is the Ponseti method, which involves weekly manipulation and casting followed by tendoachilles tenotomy and abduction bracing. Depending on patient age and deformity location, 5%-35% of patients experience recurrent deformities and require additional treatment, including casting or surgery. Dynamic supination during the swing phase of gait represents a common sequela; it can be managed with anterior tibialis transfer to the lateral foot. Variations in this technique include how much tendon is transferred, the use of 2 or 3 incisions, the recipient location of the transferred tendon, and fixation methods. Ponseti preferred the transfer of the entire anterior tibialis tendon into the ossified 3rd cuneiform and securing the transferred tendon with absorbable stitches tied over a plantar button and sterile felt. With this method, the senior author has had soft tissue complications, namely skin maceration and, on one occasion, full-thickness necrosis down to the plantar fascia. As a result, variations on this technique have evolved with resultant mitigation of these complications. These methods are described here. Key Concepts: (1) Anterior tibialis transfer (ATT) is a commonly utilized method of addressing residual deformity following the Ponseti method (2) The classic fixation method includes using an absorbable suture tied over felt and a plantar button under the cast. While uncommon, this method can lead to significant pressure sores. (3) For patients who undergo isolated ATT, we now tie the button on the outside of the cast to avoid a pressure sore. (4) In patients who undergo ATT with additional treatment of posterior contracture, one can secure the anterior tibialis into the recipient site by tying it to a K-wire used to maintain the hindfoot correction.